Strategi Komunikasi Digital by.U di Instagram Dalam Mengelola Citra Merek pada Kampanye “Gak Gitu-Gitu Aja” - Narindra Putriani Setiawan; Aan Setiadarma (Jayapangus Press, 2026)
Amid the rapid development of digital technology, the digital mobile provider by.U actively leverages Instagram features to manage its brand image. One of its key efforts is delivering promotional messages through the “Gak Gitu-Gitu Aja” campaign. Instagram features allow audiences to freely express their opinions, including both support and complaints toward the brand. This presents a challenge for by.U in responding to audience expectations and managing conversations effectively in order to maintain a positive brand image.This study aims to identify and analyze by.U’s digital communication strategy on Instagram in managing its brand image during the “Gak Gitu-Gitu Aja” campaign. The research employs a descriptive qualitative method. Data collection techniques include observation, documentation, and interviews with three internal by.U informants and two users who are also followers of @byu.id. The analysis is conducted using digital communication concepts and brand image dimensions proposed by Keller. The findings indicate that by.U implements four comprehensive stages of digital communication strategy to manage its brand image: the development of a big campaign, its transformation into a social media playbook, content publication execution, and sentiment mitigation evaluation. Validation from users and followers shows that this strategy is effective in shaping by.U’s brand image as a fun, solution-oriented, and engaging provider by leveraging various technological features on Instagram.